2011
DOI: 10.1107/s0108768110051050
|View full text |Cite
|
Sign up to set email alerts
|

Structures of two new high-pressure forms of AlPO4by X-ray powder diffraction and NMR spectroscopy

Abstract: The crystal structures of two new high-pressure AlPO(4) phases are reported. One phase synthesized at 6 GPa and 1523 K is triclinic (P1) whilst the other phase synthesized at 7 GPa and 1773 K is monoclinic (P2(1)/c). (31)P MAS (magic-angle spinning) NMR suggests three tetrahedral P sites with equal abundance in both phases. (27)Al 3Q MAS NMR spectra provided evidence for two octahedral sites and one five-coordinated Al site in each phase. The crystal structures were solved using an ab initio structure determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…Note that the pressure conditions for the syntheses of phases III (6.5 GPa) and IV (7-8 GPa) in this study are somewhat (*2 GPa) lower than those reported in Syono et al (1971). This could be due to difference in pressure calibration: the pressure calibration of Syono et al (1971) was done at room temperature and that used in the present study was performed under high pressure and high temperature conditions using synchrotron radiation (Kanzaki et al 2011).…”
Section: Sample Synthesis and Descriptionmentioning
confidence: 59%
See 1 more Smart Citation
“…Note that the pressure conditions for the syntheses of phases III (6.5 GPa) and IV (7-8 GPa) in this study are somewhat (*2 GPa) lower than those reported in Syono et al (1971). This could be due to difference in pressure calibration: the pressure calibration of Syono et al (1971) was done at room temperature and that used in the present study was performed under high pressure and high temperature conditions using synchrotron radiation (Kanzaki et al 2011).…”
Section: Sample Synthesis and Descriptionmentioning
confidence: 59%
“…The temperature was measured with a W 97 Re 3 -W 75 Re 25 thermocouple with uncertainties within ca 2 K. For samples #2 and #5, the temperature was estimated from the heating power with uncertainties within ca 100 K because the thermocouple failed. The pressure was estimated from a pressure calibration curve constructed from an in situ X-ray diffraction study with the same pressure cell (Kanzaki et al 2011) with an uncertainty of less than 0.5 GPa.…”
Section: Sample Synthesis and Descriptionmentioning
confidence: 99%
“…K -cymrite was then synthesized at 5 GPa and 800 °C for 2 hrs using a Kawai -type multi -anvil press. The procedure for the high -pressure and high -temperature experiments is identical to that reported in Kanzaki et al (2011). The anhydrous form (kokchetavite) was produced at ambient pressure by heating K -cymrite at 550 °C for 1hr.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, berlinite may well be applicable as pressure sensor at higher pressures than quartz, because the high‐pressure analogues of coesite, stishovite, and post‐stishovite in the system AlPO 4 have not yet been reported . However, three new triclinic or monoclinic AlPO 4 high‐pressure phases have recently been synthesized between 5 to 7 GPa and 1000°C to 1500°C . In a few systems, berlinite forms solid solutions by substitution of Al with B, Ga, or Fe and of PO 4 by AsO 4 , with substantial effects on the frequency of some Raman modes .…”
Section: Introductionmentioning
confidence: 99%